RISK FACTORS OF STUNTING IN THE SUB-DISTRICT OF SOUTH WAKORUMBA MUNA REGENCY: Stunting Risk Factor - Rince Maripadang; Sunarsih Sunarsih; Sultan Akbar Toruntju (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: Malnutrition is the cause of one third of deaths in children. Nutritional Status Monitoring data in Muna Regency obtained 1,279 cases of stunting in toddlers aged 0-24 months and 1,397 cases in toddlers 24-59 months.The high incidence of stunting is caused by several factors. This research aims to analyzing risk factors for stunting in South Wakorumba District, Muna Regency, Southeast Sulawesi Province. Methods: This type of research is a case control study conducted from March to April 2021,the sample used are 63 cases taken by simple random sampling and 63 controls. Results: Using Odds Ratio (OR). OR value of family income is 0,294< 1, OR value of dietary habit is 0,323< 1, OR value of exclusive breastfeeding history is 0,327< 1, OR value of LBW history is 0,359< 1, and OR value of history of infection is 0,229< 1. Conclusion: Family income, dietary habit, exclusive breastfeeding history, LBW history, and history of infection are risk factors of stunting incident in South Wakorumba District, Muna Regency, Southeast Sulawesi Province.